A Comprehensive Systematic Review of Social Determinants in Maternal Mortality Rates in Developing Countries - Maria Ayu Florenza Monar; Prilly Parrhesia Edong Rumissing (International Medical Journal Corp. Ltd, 2026)
Introduction: Maternal mortality remains a critical public health challenge in developing countries, where 94% of global maternal deaths occur. Social determinants—including education, poverty, geographic access, gender inequality, and health system quality—drive persistent disparities. This systematic review synthesizes evidence on these determinants to identify priority interventions. Methods: We screened 80 studies (RCT, etc) from Sub-Saharan Africa, South Asia, Southeast Asia, Latin America, and the Middle East. Inclusion criteria required quantitative data on social determinants and maternal mortality outcomes in World Bank-defined developing countries. Data extraction focused on seven domains: study setting, social determinants, maternal mortality measurement, associations, interventions, barriers, and key findings. Results: Low maternal education showed the strongest individual-level association, with relative risks of 3.2 (95% CI: 1.5–6.9) for no formal education versus secondary education [1]. Female literacy rate was the strongest national-level predictor in the Eastern Mediterranean (β = −1.045, p < 0.01), exceeding GDP per capita [2]. Household poverty was associated with hazard ratios of 3.92 (95% CI: 1.01–15.3) in rural South Africa [4] and 94.8% of maternal deaths in Pakistan occurred among poor women [60]. Geographic barriers dominated Sub-Saharan Africa and rural Nepal, with transportation delays reported in 84.6% of African studies [6]. The three-delays model showed continental patterning: Delay 1 (decision-making) dominates Asia, Delay 2 (transport/geography) dominates Africa, and Delay 3 (quality of care) dominates Latin America [7]. Health system failures contributed to 80.8% of deaths in African facilities [6]. Community-based interventions including birth preparedness (≥30% coverage reduced mortality by 53%, RR = 0.47; 95% CI: 0.26–0.87) and emergency transport loans showed effectiveness [15,41]. Discussion: Education, poverty, and geographic access are consistently the most powerful determinants across all settings, but their relative importance shifts with economic development. In low-income rural settings, geographic distance and transport are binding constraints; in middle-income urbanizing contexts, health system quality and governance become paramount. Indonesia-specific evidence is limited but suggests high institutional delivery coverage (91.8% of deaths occurred in facilities in Bali) has shifted the bottleneck from access to quality of care [14]. The absence of Papua-specific studies represents a critical evidence gap. Conclusion: Reducing maternal mortality in developing countries requires multi-level interventions that simultaneously address education, poverty, transport, and health system quality. Priority actions include: (1) sustaining female secondary education, (2) scaling community-based transport financing, (3) improving facility readiness for emergency obstetric care, and (4) targeting interventions to the predominant delay pattern in each region. Research is urgently needed in remote Indonesian regions such as Papua.